The Influence of Physical Education on Self-Efficacy in Overweight Schoolgirls: A 12-Week Training Program - Latino, Francesca; Cataldi, Stefania; Bonavolontà, Valerio; Carvutto, Roberto; De Candia, Michele; Fischetti, Francesco (Frontiers in Psychology, 2021)
The purpose of this randomized controlled study was to investigate the impact of a 12-week physical education (PE) program on the self-efficacy of overweight schoolgirls. We randomly assigned 60 overweight schoolgirls (15–17 years) to either an experimental moderate to vigorous aerobic exercise (∼90 min, three times a week) group (n = 30) or a control group (CG) (n = 30) that received non-specific regular PE lessons with activities chosen by the curricular teacher mainly focused on team games and sports skills that aimed to achieve general psycho-physical wellness (∼90 min, three times a week). To assess the starting level of students and significant changes reached, at baseline and after training, a battery of standardized assessment motor tests and a psychometric scale (generalized self-efficacy scale, GES) were administered. At the end of the intervention, the experimental group reported a considerable decrease in body mass index (BMI) and a large improvement in self-efficacy (p < 0.001). No significant changes were found in the CG. The results suggested that the 12-week moderate to a vigorous aerobic exercise program is an effective weight loss intervention and a vehicle to promote a range of outcomes important to the qualitative growth of adolescents. In fact, it could provide a positive and significant impact on the self-efficacy of overweight schoolgirls.